Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations CLEANLINESS OF HEAD, TEETH, AND NOSE 31 it will be found possible to arrange for the presentation of relevant material at all stages of the child's school life, [Image with caption: Where there's DIRT there's DANGER] Reproduction of Health and Cleanliness Council's Poster (P. 3), 7½" x 20", in black, white, and red. Also available as Transparency for windows, etc. (T. 1). and to stabilise the habits formed in the first instance through self-assertion, "vanity," imitation, love and respect for the teacher, the desire of verbal approval in presence of schoolfellows, and the like, by enabling the pupil to add to these primary motives others which are [photograph] Performance of the Council's propaganda play "A Health Pageant," by the scholars of an L.C.C. Infants' School. based upon accurate information and the growth of a communal sense, which receive rational and ethical approval. 177/5/8/3